DD-014 Study of the reduction in the rate of dispensing errors following the installation of an automated delivery robot. (24th February 2014) - Massé, C; Vitale, G; Gavard, A; Desplechain, M; Jouglen, J
Abstract : Background: Automation and computerisation of the different steps and stages from prescription to drug administration have decreased the iatrogenic risks of drugs. Meanwhile, it is important to analyse robotic preparation and delivery compared to manual. Purpose: To identify and analyse any weaknesses in the robotic system before correcting them. Materials and methods: 10, 202 unit doses were analysed by checking the final containers before sending them to care units: 9437 had been prepared by the robot while 765 had been manually prepared by the pharmaceutical team. Errors were therefore divided into two groups: either robot-related or human-related. Results: Among the 10, 202 unit doses prepared, 17 preparation errors were reported (error rate: 0.16%). Four of them were intercepted by the pharmaceutical team adding manual complements with barcode readers. So finally, only thirteen errors were reported at the end of the production process (error rate: 0.13%). Eight errors were robot-related among the 9437 unit doses prepared by the robot (error rate: 0.08%). Five errors were human-related among the 765 unit doses manually prepared (0.65%). Conclusions: In the literature, the error rate of a manual preparation of prescriptions varies from 0.8% to 2.9%. In our hospital, a previous study estimated it at 1%. Robotic production is much less prone to error and could be a good way of observing the law about medication safety. No conflict of interest.